Synthesis of the 1,5-disubstituted tetrazole-methanesulfonylindole hybrid system via high-order multicomponent reaction - Cesia M. Aguilar-Morales; América A. Frías-López; Nadia V. Emilio-Velázquez; Alejandro Islas-Jácome; Angelica Judith Granados-López; Jorge Gustavo Araujo-Huitrado; Yamilé López-Hernández; Hiram Hernández-López; Luis Chacón-García; Jesús Adrián López; Carlos J. Cortés-García (Beilstein Journal of Organic Chemistry)
A series of 1,5-disubstituted tetrazole-indole hybrids were synthesized via a high-order multicomponent reaction consisting of an Ugi-azide/Pd/Cu-catalyzed hetero-annulation cascade sequence. This operationally simple one-pot protocol allowed high bond-forming efficiency and creating six new bonds (two C–C, three C–N, and one N–N). Additionally, the products were evaluated against breast cancer MCF-7 cells, finding moderate activity in the compounds substituted with fluorine and chlorine.